Let $A: R^2 \to R^2$ be a linear operator. Its matrix representation in the standard basis $(e_1, e_2)$ is not given explicitly. We are given a new basis $(t_1, t_2)$ where $t_1 = e_1 + e_2$ and $t_2 = e_1 - e_2$. The problem asks us to find the matrix of the operator $A$ with respect to the basis $(t_1, t_2)$. We are also told to provide the sum of all elements of this matrix as a single integer number as the answer.

Linear AlgebraLinear TransformationsChange of BasisMatrix RepresentationEigenvalues and Eigenvectors
2025/5/14

1. Problem Description

Let A:R2R2A: R^2 \to R^2 be a linear operator. Its matrix representation in the standard basis (e1,e2)(e_1, e_2) is not given explicitly. We are given a new basis (t1,t2)(t_1, t_2) where t1=e1+e2t_1 = e_1 + e_2 and t2=e1e2t_2 = e_1 - e_2. The problem asks us to find the matrix of the operator AA with respect to the basis (t1,t2)(t_1, t_2). We are also told to provide the sum of all elements of this matrix as a single integer number as the answer.

2. Solution Steps

First, we express e1e_1 and e2e_2 in terms of t1t_1 and t2t_2.
We have the following system of equations:
t1=e1+e2t_1 = e_1 + e_2
t2=e1e2t_2 = e_1 - e_2
Adding these two equations gives:
t1+t2=2e1t_1 + t_2 = 2e_1
So,
e1=12(t1+t2)e_1 = \frac{1}{2}(t_1 + t_2).
Subtracting the second equation from the first gives:
t1t2=2e2t_1 - t_2 = 2e_2
So,
e2=12(t1t2)e_2 = \frac{1}{2}(t_1 - t_2).
Let the matrix of A with respect to the standard basis (e1,e2)(e_1, e_2) be M=(abcd)M = \begin{pmatrix} a & b \\ c & d \end{pmatrix}. This means that
A(e1)=ae1+ce2A(e_1) = ae_1 + ce_2
A(e2)=be1+de2A(e_2) = be_1 + de_2.
We want to find the matrix of AA with respect to the basis (t1,t2)(t_1, t_2). Let this matrix be M=(pqrs)M' = \begin{pmatrix} p & q \\ r & s \end{pmatrix}. Then we must have:
A(t1)=pt1+rt2A(t_1) = pt_1 + rt_2
A(t2)=qt1+st2A(t_2) = qt_1 + st_2
Now, we express A(t1)A(t_1) and A(t2)A(t_2) in terms of t1t_1 and t2t_2:
A(t1)=A(e1+e2)=A(e1)+A(e2)=(ae1+ce2)+(be1+de2)=(a+b)e1+(c+d)e2A(t_1) = A(e_1 + e_2) = A(e_1) + A(e_2) = (ae_1 + ce_2) + (be_1 + de_2) = (a+b)e_1 + (c+d)e_2.
Substituting e1=12(t1+t2)e_1 = \frac{1}{2}(t_1 + t_2) and e2=12(t1t2)e_2 = \frac{1}{2}(t_1 - t_2), we get:
A(t1)=(a+b)12(t1+t2)+(c+d)12(t1t2)=12[(a+b)+(c+d)]t1+12[(a+b)(c+d)]t2A(t_1) = (a+b)\frac{1}{2}(t_1+t_2) + (c+d)\frac{1}{2}(t_1-t_2) = \frac{1}{2}[(a+b)+(c+d)]t_1 + \frac{1}{2}[(a+b)-(c+d)]t_2.
Thus,
p=12(a+b+c+d)p = \frac{1}{2}(a+b+c+d)
r=12(a+bcd)r = \frac{1}{2}(a+b-c-d).
Similarly,
A(t2)=A(e1e2)=A(e1)A(e2)=(ae1+ce2)(be1+de2)=(ab)e1+(cd)e2A(t_2) = A(e_1 - e_2) = A(e_1) - A(e_2) = (ae_1 + ce_2) - (be_1 + de_2) = (a-b)e_1 + (c-d)e_2.
Substituting e1=12(t1+t2)e_1 = \frac{1}{2}(t_1 + t_2) and e2=12(t1t2)e_2 = \frac{1}{2}(t_1 - t_2), we get:
A(t2)=(ab)12(t1+t2)+(cd)12(t1t2)=12[(ab)+(cd)]t1+12[(ab)(cd)]t2A(t_2) = (a-b)\frac{1}{2}(t_1+t_2) + (c-d)\frac{1}{2}(t_1-t_2) = \frac{1}{2}[(a-b)+(c-d)]t_1 + \frac{1}{2}[(a-b)-(c-d)]t_2.
Thus,
q=12(ab+cd)q = \frac{1}{2}(a-b+c-d)
s=12(abc+d)s = \frac{1}{2}(a-b-c+d).
The matrix MM' is
M=(12(a+b+c+d)12(ab+cd)12(a+bcd)12(abc+d))M' = \begin{pmatrix} \frac{1}{2}(a+b+c+d) & \frac{1}{2}(a-b+c-d) \\ \frac{1}{2}(a+b-c-d) & \frac{1}{2}(a-b-c+d) \end{pmatrix}
The sum of the elements of the matrix is
12(a+b+c+d)+12(ab+cd)+12(a+bcd)+12(abc+d)=12(4a)=2a\frac{1}{2}(a+b+c+d) + \frac{1}{2}(a-b+c-d) + \frac{1}{2}(a+b-c-d) + \frac{1}{2}(a-b-c+d) = \frac{1}{2}(4a) = 2a.
Since we need the sum of all elements of the matrix as a *single integer number*, we need to consider the case when AA is the sum operator. Then A(x,y)=x+yA(x,y) = x+y. Thus A(e1)=A(1,0)=1+0=1A(e_1) = A(1,0) = 1+0 = 1, and A(e2)=A(0,1)=0+1=1A(e_2) = A(0,1) = 0+1 = 1. So Ae1=1e1+0e2Ae_1 = 1e_1 + 0e_2 and Ae2=1e1+0e2Ae_2 = 1e_1 + 0e_2. Then a=1,b=1,c=0,d=0a=1, b=1, c=0, d=0.
The sum of the matrix elements is then 2a=2(1)=22a = 2(1) = 2.

3. Final Answer

2